Chemical structural and chain conformational characterization of some bioactive polysaccharides isolated from natural sources - Yang, Liqun; Zhang, Li-Ming (Carbohydrate polymers, 2009)
Some polysaccharides isolated from natural sources show various important biological activities, such as antitumor, immunomodulatory, and anti-inflammatory effects, which are strongly affected by their chemical structures and chain conformations. This article attempts to review the current development on structural and conformational characterization of some importantly bioactive polysaccharides isolated from natural sources. The chemical structures were analyzed by FTIR, liquid-state NMR (one and two dimensions), solid-sate NMR, Raman spectroscopy, gas chromatography (GC), GC–Mass (GC–MS), and high-performance liquid chromatography (HPLC). The chain conformations of polysaccharides in solutions were investigated using static and dynamic light scattering, viscosity analysis based on the theory of dilute polymer solution, circular dichroism analysis, atomic force microscopy (AFM) including single molecular AFM and AFM-based single-molecule force spectroscopy, fluorescence correlation spectroscopy and NMR spectroscopy.